Identifying victims and types of Gender Based Violence among survivors visiting One-Stop Crisis Management Center(OCMC) of Bharatpur Hospital - Pariyar, Jewan; Lamichanne, Bigyan; Agrahari, Mahendra Kumar; Sah , Kamlesh Kumar; Poudel, Yubraj; Shah, Nischal; Upadhya, Hari Prassad (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Gender-based violence (GBV) is a significant global issue that affects individuals across various age groups, genders, and ethnicities. In Nepal, the healthcare system plays a crucial role in providing immediate support to survivors of GBV, particularly through specialized services like One-Stop Crisis Management Centers (OCMC).Method: A retrospective cross sectional study conducted in Bharatpur Hospital from fiscal year 2076/77 to 2078-79 among 695 survivors. The data were analyzed using Microsoft Excel tool.Result: The study revealed a predominance of female survivors (98.99%) and a significant representation from the 19-49 years age group (44.46%). The most common forms of violence were rape (45.32%), followed by attempted rape (12.23%) and physical assault (12.09%). The majority of referrals came from police sources (33.81%).Conclusion: This study revealed the critical role of One-Stop Crisis Management Centers in providing comprehensive care to survivors of gender-based violence. The findings highlight the need for targeted interventions that address the specific needs of different demographic groups, particularly marginalized ethnic communities and female survivors.